Late‐onset Proteus syndrome with cerebriform connective tissue nevus and subsequent development of intraductal papilloma. Issue 9 (20th April 2022) - Modlin, Emily W.; Slavotinek, Anne M.; Darling, Thomas N.; Lipkowitz, Stanley; Barr, Frederic G.; Munster, Pamela N.; Biesecker, Leslie G.; Ours, Christopher A.
Abstract: Proteus syndrome (PS) is a rare segmental overgrowth disorder caused by a mosaic activating variant in AKT1 . The features of PS are often not present at birth but develop during the first few years of life. We describe a 55‐year‐old female, whose first symptom of overgrowth, a cerebriform connective tissue nevus, occurred at 19 years of age. We report the identification of the AKT1 c.49G > A p.(Glu17Lys) variant in this progressive lesion, the bony overgrowth, and recurrence after surgical intervention. In the sixth decade of life, this individual developed intraductal papillomas within her right breast which were confirmed to contain the same activating AKT1 variant as the connective tissue nevus. While similar neoplasms have been described in an individual with Proteus syndrome, none has been evaluated for the presence of the AKT1 variant. The tumor also contained two likely pathogenic variants in PIK3R1, c.1392_1403dupTAGATTATATGA p.(Asp464_Tyr467dup) and c.1728_1730delGAG p.(Arg577del). The finding of additional genetic variation putatively affecting the PI3K/AKT pathway in the neoplastic tissue may provide preliminary evidence of a molecular mechanism for tumorigenesis in PS. The late onset of symptoms and molecular characterization of the breast tumor expand the clinical spectrum of this rare disorder.